Augmented Reality-Assisted Manual Packing Optimization - Rondon-Usma, Angie Valeria; Camacho-Muñoz, Guillermo A.; Álvarez-Martinez, David (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
The process of packing—organizing products within a container to optimize available space—is often performed manually without technological assistance, which can lead to inconsistent efficiency and occasional errors. While augmented reality (AR) has been explored to support packing tasks, prior research has largely relied on static final-pose overlays and has rarely integrated advanced packing optimization algorithms. This paper presents OPTAR, a novel packing assistance system that combines a 3D packing optimization algorithm with trajectory-based AR pose guidance, deployed on the Microsoft HoloLens 2. We describe the system’s design, implementation, and evaluation through experiments comparing two methods: a packing operation with and without OPTAR. Results indicate that OPTAR assistance significantly improves space utilization, eliminates misplaced items, though with longer task completion times during initial use. To strengthen the generalizability of our findings to industrial applications, future work will extend testing to real industrial environments, involve professional packing operators, and larger sample sizes.